Advanced mist blower technology for efficient disease management in rubber plantations - Mathew J; Mushrif K.S; Patel J.S; Prem E; Vijayan K (Rubber Board Bulletin, 2014)
Abnormal leaf fall (ALF) caused by Phytophthora spp. ia an annually occuring fungal disease in the traditiional rubber growing regions in India. Prophylactic ground spraying of copper oxychloride in agiculture spray oil using mist blowers is the conventional practice to manage this disease. Owing to paucity of labourers, the labour intensive ground spraying operations have become less attractive. Therefore, various alternative ground spraying systems were attempted. The blower assembly of the conventional mist blower having 4.5 hp capacity was attached to a mini tractor. The power for operating the sprayer was provided by the power take off (PTO) shaft of the tractor. This system was field tested by conducting prophylactic spraying of COC in oil against ALF disease. There was a no significant difference with respect to leaf retention between the use of conventional mist blower and that of the tractor mounted mist blower. Therefore, the atomizer, which determines the delivery height of the spray fluid was changed and a modified one was fitted. This system was also field tested and was found to attain comparatively more delivery height than both the conventionl mist blower assembly with ordinary atomizer fitted on the tractor and thatoperated by four persons. certain defects were also noticed in the system during field operation. The spraying attachment was connected with the PTO by a lengthy shaft due to which a 30 cm gap occurred between PTO and the attachment. This caused frequent slip of propeller shaft frequently while moving on uneven terrain. Moreover, though the power output of the tractor was 18 hp, the capicity of the blower unit was only 4.5 hp. Owing to this incompatibility, the expected discharge height could not be attained. In order to overcome these defects, the spraying attachment was connected directly to the PTO shaft of the tractor using a single gear-wheeled gear box assembly, and a blower assembly having 12 hp capacity was designed and attached. The modified system was tested in the field and was found to attain a delivery height of 26.8m with a leaf retention of 50;while that with the conventional mist blower was only 30;. The improved mini tractor mounted mist blower was found very effective for the plant protection in the rubber plantations of India, owing to less labour requirement and more area covered in unit time.
Keywords: Disease management; Mist blower technology; Rubber plantations